Clairaut slant submersion from almost Hermitian manifolds - Kumar Sushil; Prasad Rajendra; Kumar Singh Punit (Mathematica Moravica)
Our main aim is to introduce Clairaut slant submersions in complex geometry. We give the notion of Clairaut slant submersions from almost Hermitian manifolds onto Riemannian manifold in this article. We obtain some basic results on discussed submersions. Furthermore, we provide some examples to explore the geometry of Clairaut slant submersions.